Multiple omics revealed the growth-promoting mechanism of Bacillus velezensis strains on ramie - Wang, Xin; Wang, Yanzhou; Fu, Yafen; Zhai, Yang; Bai, Xuehua; Liu, Tongying; Li, Guang; Zeng, Liangbin; Zhu, Siyuan (Frontiers in Plant Science, 2024)
Beneficial bacteria that promote plant growth can shield plants from negative effects. Yet, the specific biological processes that drive the relationships between soil microbes and plant metabolism are still not fully understood. To investigate this further, we utilized a combination of microbiology and non-targeted metabolomics techniques to analyze the impact of plant growth-promoting bacteria on both the soil microbial communities and the metabolic functions within ramie (Boehmeria nivea) tissues. The findings indicated that the yield and traits of ramie plants are enhanced after treatment with Bacillus velezensis (B. velezensis). These B. velezensis strains exhibit a range of plant growth-promoting properties, including phosphate solubilization and ammonia production. Furthermore, strain YS1 also demonstrates characteristics of IAA production. The presence of B. velezensis resulted in a decrease in soil bacteria diversity, resulting in significant changes in the overall structure and composition of soil bacteria communities. Metabolomics showed that B. velezensis significantly altered the ramie metabolite spectrum, and the differential metabolites were notably enriched (P < 0.05) in five main metabolic pathways: lipid metabolism, nucleotide metabolism, amino acid metabolism, plant secondary metabolites biosynthesis, and plant hormones biosynthesis. Seven common differential metabolites were identified. Correlation analysis showed that the microorganisms were closely related to metabolite accumulation and yield index. In the B. velezensis YS1 and B. velezensis Y4-6-1 treatment groups, the relative abundances of BIrii41 and Bauldia were significantly positively correlated with sphingosine, 9,10,13-TriHOME, fresh weight, and root weight, indicating that these microorganisms regulate the formation of various metabolites, promoting the growth and development of ramie. Conclusively, B. velezensis (particularly YS1) played an important role in regulating soil microbial structure and promoting plant metabolism, growth, and development. The application of the four types of bacteria in promoting ramie growth provides a good basis for future application of biological fertilizers and bio-accelerators.